2012
DOI: 10.1007/s12098-012-0784-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Severe Influenza A (H1N1) Virus Infection

Abstract: During late stage of pandemic wave, the majority of patients were young children. Children with severe Influenza A (H1N1) are prone to develop complications, and die from ARDS. If influenza-like illness is accompanied by neurologic signs, influenza A (H1N1) virus infection should be considered. The viral shedding in children is longer than in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The percentage of ICU treatment in the pandemic season was consistent with the results reported by Gastañaduy and Bégué (9%), but higher than reported by German authors (6%) 35,36 . In the post-pandemic season, the incidence of severe forms of disease and mortality in hospitalized children was extremely low (2.3%), even in those with risk factors for development of complications, which was consistent with the reports from Spain and China 39,40 . Most of our children were free from risk factors in both seasons (57.8% and 77.3%), as also found in several American and European centers 41,42 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The percentage of ICU treatment in the pandemic season was consistent with the results reported by Gastañaduy and Bégué (9%), but higher than reported by German authors (6%) 35,36 . In the post-pandemic season, the incidence of severe forms of disease and mortality in hospitalized children was extremely low (2.3%), even in those with risk factors for development of complications, which was consistent with the reports from Spain and China 39,40 . Most of our children were free from risk factors in both seasons (57.8% and 77.3%), as also found in several American and European centers 41,42 .…”
Section: Discussionsupporting
confidence: 88%
“…The most common complication in children was primary viral pneumonia (15.6% vs. 3.6%) in the first season and bacterial pneumonia (22% vs. 12.5%) in the second season. In our setting, there were complications such as encephalopathy, neurological disorders and gastroenteritis, which are reported by Chen et al 40 . Otitis media as the most common complication of influenza in children was rarely observed, which can be explained by the fact that pandemic influenza generally has less bacterial complications 42,43 .…”
Section: Discussionsupporting
confidence: 63%
“…It is well known that cytokine storm plays a major role in pneumonia and ARDS (Thiel and Weber, 2008). The clinical study showed a slight increase of IL-6, IL-10 and TNF-α and high levels of IFN-γ and MCP-1 in patients with ARDS caused by H1N1 infection (Bermejo-Martin et al, 2009;Chen et al, 2013). TNF-α is believed to be one of the most prominent inflammatory cytokines in causing ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 2,147 children with lower respiratory infection due to RSV, Rodriguez et al reported age less than 6 months, history of prematurity, chronic respiratory disease or congenital heart disease, and coinfection with adenovirus were significant predictors of increased disease severity (74). Similar predictors exist for children infected with influenza A (H1N1) virus, including age less than 5 years, a history of chronic lung disease, congenital heart disease, and immune compromise (Table 1) (75). It is therefore prudent that clinicians should conduct laboratory evaluations early in the illness for viral infections in these at-risk populations presenting with respiratory failure and ARDS.…”
Section: Diagnosis Of Viral-induced Ardsmentioning
confidence: 91%